Análisis, diseño e implementación del módulo control de procesos de gestión y apoyo del sistema estratégico de calidad de compulead s.a. - Cedillo Viera, Franklin Manuel (2010)
Compulead S.A. is an Ecuadorian company that provides information technology services to their customers. The need of this company to seek international markets and the exigency of this markets that demands quality of services have led to the implementation of the Strategic Quality System (10 years ago). To make quality management more efficient, an Information System had been developed that contains de module Control of the Management and Support Process (CPGA).In it, there are registered all the company internal operation activities and thus make easy to keep track and control of activities as well as control the used resources such as employees, materials, money and time. As a result of the system deploy, Compuled S.A. achieved improving the quality management process, automating it and involving their employees feeding the system, this permits to obtain indicators through the evaluation module that allows process managers to make strategic decisions.